Service thinking the seven principles to discover innovative opportunities - Hastings, Hunter; Saperstein, Jeff (Service systems and innovations in business and society collection., 2014)
Business paradigm shifts are rare. However, the shift to a service-dominant economy and to service-dominant value creation genuinely merits such a designation, both on the surface through the lens of traditional economic measures and even more deeply and profoundly through the lens of Vargo and Lusch's Service-Dominant Logic (S-D Logic). Almost 80% of GDP in developed economies is attributable to services, and some economists regard products as merely the physical embodiment of service delivery. Yet today's business analysis, business management, business organization, business processes, and business education emerged from a manufacturing-dominant logic; the principles of service are often underserved and poorly understood. This results in lost opportunities for growth.